Methodology and Practical Tools for Digital Transformation of High-tech Enterprises - M. M. Batova; I. V. Baranova; S. V. Mayorov; O. V. Korobchenko (Модернизация, инновация, развитие, 2019)
Purpose: the aim of the article is to develop a methodology and practical tools for effective digital transformation of high-tech enterprises. To achieve this goal, a concept of enterprise transformation by means of innovative modernization, affecting changes in products, technological operations and organizational and production structures, was developed. For this, a number of tasks were solved, including the development of original economic and mathematical models that describe the change in the functional business strategies of a high-tech enterprise; selection and formalization of model variables; development of organizational design methods for flexible robotic structures and models for determining the parameters of flexibility and productivity of a robotic structure; software development of digital transformation processes.Methods: in preparing the article, methods of systems theory, project management of an innovative focus, mathematical modeling and a number of other methods were used.Results: a set of information systems for decision support in the areas of design and economic activities of a high-tech enterprise has been developed. The design of such systems was due to a number of circumstances. Firstly, the need to transform traditional information technologies used in the practice of a high-tech enterprise into digital information technologies. Secondly, the need for a high-tech enterprise in original applied software applications that provide solutions to innovative and economic problems, taking into account the specifics of the enterprise. To do this, an analysis was performed and models of data collection and storage were proposed for solving the problems of information support of the economic activity of a high-tech enterprise. The possibility of using a consistent data model in organizing the management of receivables and payables is shown. Cross-platform software was developed for the support system for decisions made by a high-tech enterprise, and a convenient user interface was implemented.Conclusions and Relevance: the study showed that it is advisable to create information systems as hierarchical structures covering the strategic, tactical and operational levels of management. In order to bring the automation level of the control and production subsystems into conformity, industrial robotics must be integrated into the created production links.